A Study On The Use of Crude Palm Oil Futures As An Effective Hedging Tool For The Malaysian Palm Oil Producers and Refiners - Rosalan Ali (Asian Academy of Management Journal, 1998)
A Study On The Use of Crude Palm Oil Futures As An Effective Hedging Tool For The Malaysian Palm Oil Producers and Refiners (PDF not available)